Knowledge audit: the Agensi Antidadah Kebangsaan organizational case study - Abdullah, Mohd Syazwan; Mat Ali, Abdul Bashah; Hibadullah, Cik Fazilah; Wahid, Juliana; Hassan, Syahida (2012)
The paper discusses the knowledge audit conducted at Agensi Antidadah Kebangsaan Malaysia to evaluate the knowledge management practices in treatments of drug addicts and to gather insights into the types of knowledge that is important in providing necessary treatments to drug addicts.The audit evaluation was carried out using the components of Knowledge Audit such as Knowledge Need Analysis, Knowledge Inventory Analysis, Knowledge Flow Analysis and Knowledge Mapping based on the KeKMa methodology for knowledge audit.The findings from the evaluation indicates the need for incorporating knowledge management in managing the treatments provided at these centers and the feasibility for the implementation of integrated workflow system that would enhance the operations of these centers to provide effective care and treatment in the near future.